2011
DOI: 10.1016/j.neuron.2011.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences on Cortical Regionalization in the Human Brain

Abstract: Summary Animal data demonstrate that the development of distinct cortical areas is influenced by genes that exhibit highly regionalized expression patterns. In this paper, we show genetic patterning of cortical surface area derived from MRI data from 406 adult human twins. We mapped genetic correlations of areal expansion between selected seed regions and all other cortical locations, with the selection of seed points based on results from animal studies. “Marching seeds” and a data-driven, hypothesis-free, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
133
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 32 publications
14
133
1
Order By: Relevance
“…The present results are coherent with such experimental findings, in that they suggest that the ability to remember and imagine with a higher degree of self-presence, or autonoetic consciousness, is related to default-network connectivity independently of the task used to elicit the memories and imaginations. Other recent studies have also demonstrated such relationships in adults, indicating, for instance, that high functional connectivity is related to memory performance (16,37,38) and occurrence of spontaneous thoughts (14). An interesting difference between these studies and the present developmental study is the negative relationship found.…”
Section: Functional Connectivity and Vivid Experiences Of Past And Fucontrasting
confidence: 66%
See 2 more Smart Citations
“…The present results are coherent with such experimental findings, in that they suggest that the ability to remember and imagine with a higher degree of self-presence, or autonoetic consciousness, is related to default-network connectivity independently of the task used to elicit the memories and imaginations. Other recent studies have also demonstrated such relationships in adults, indicating, for instance, that high functional connectivity is related to memory performance (16,37,38) and occurrence of spontaneous thoughts (14). An interesting difference between these studies and the present developmental study is the negative relationship found.…”
Section: Functional Connectivity and Vivid Experiences Of Past And Fucontrasting
confidence: 66%
“…To allow integration of functional and structural aspects of the brain, volume of the hippocampus and local arealization of the cerebral cortex were included in an additional analysis. Local arealization was chosen because this measure has received much recent attention and has shown to be of great interest as a metric of cortical structure (16)(17)(18)(19).A total of 103 children and adolescents (age, 9.1-21.9 y) were tested with a recall-imagination cue-word task. Children's ability to imagine the future has been subject of several recent studies (20)(21)(22)(23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This variation is significantly greater than variation in total cortical area, and therefore, both the absolute area and proportion of the cortical sheet allocated to processing vision varies between individuals. Moreover, a recent human twin study showed strong genetic correlations between the area of V1 and the remainder of occipital cortex but not other cortical lobes (9), suggesting that occipital visual areas share common genetic influences. However, it is still largely unknown what specific genetic and environmental factors contribute to normal variation in the absolute and proportional size of occipital cortex.…”
Section: −8mentioning
confidence: 99%
“…Although spatial proximity is likely to be a primary factor constraining gene expression across the cerebral cortex (54,55), the current analysis presents a different perspective: relative expression patterns of a small number of genes that are uniquely expressed in human upper cortical layers compared with mouse are correlated in distributed patterns across the cerebral cortex. Their spatial distributions across the cortex are closely linked to cortical subtypes and their associated connectivity profiles.…”
Section: And 7)mentioning
confidence: 99%